Well-being: pathway to life satisfaction among older persons in Ghana - Joseph Kojo Oduro; Mary Ama Oduro (BMC Geriatrics)
Abstract Background Globally, the number of older people is rising. However, few studies have examined well-being as the pathway to higher life satisfaction of older persons in Ghana. Methods The study used longitudinal data from the 2014/15 Study of Global Ageing and Adult Health (SAGE) Wave 2 to investigate factors of high life satisfaction among older persons in Ghana. The data was analysed using a multilevel logistic regression model, taking into account both individual-level characteristics and community-level variables. The model's output was presented as odds ratios (OR), to show the likelihood of high life satisfaction based on various well-being measures, revealing which components of well-being have the greatest influence on life happiness in older persons. Results High levels of emotional (OR=1.67, 95% CI=1.25, 2.23), psychological (OR=1.60, 95% CI=1.21, 2.12), and spiritual (OR=2.36, 95% CI=1.72, 3.25) well-being were associated with higher odds of high life satisfaction. Conversely, a high level of physical well-being was linked to lower odds of high life satisfaction (OR=0.75, 95% CI=0.56, 1.01). Conclusion The higher the levels of emotional, psychological, and spiritual well-being, the higher the life satisfaction of older persons 60 years and older. However, the higher the level of self-reported physical well-being, the less likely to experience high life satisfaction. Emphasis should be on high physical well-being, promoting high life satisfaction and healthy ageing among older persons in Ghana.